2003
DOI: 10.1590/s0034-89102003000500013
|View full text |Cite
|
Sign up to set email alerts
|

Pacientes que se beneficiam de internação psiquiátrica em hospital geral

Abstract: Resumo ObjetivoA internação psiquiátrica, embora onerosa, continua sendo um recurso terapêutico indispensável para pacientes graves. A internação em unidades psiquiátricas de hospital geral (UPHG) tem sido recomendada como a melhor alternativa aos macro-hospitais psiquiátricos. Nesse sentido, realizou-se estudo com o objetivo de verificar variáveis socioeconômicas e clínicas associadas com o êxito ou o fracasso da internação. Métodos Foram revistos dados sociodemográficos e clínicos de 1.463 pacientes internad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
6
0
28

Year Published

2007
2007
2015
2015

Publication Types

Select...
4
4

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(42 citation statements)
references
References 5 publications
(8 reference statements)
3
6
0
28
Order By: Relevance
“…Such data are consistent with those found in the research findings of Cardoso and Galera (2011), Conde Diaz et al (2009) and Dalgalarrondo et al (2003). In every hospital analyzed, the diagnosis focuses on the medical assessment, being conducted unilaterally by the prescriptions provided by their psychiatrists with views to the information collected, allowing the mitigation of psychic disorganization characteristic of crisis situations.…”
Section: Analysis Axis II -Diagnostic Criteriasupporting
confidence: 88%
See 1 more Smart Citation
“…Such data are consistent with those found in the research findings of Cardoso and Galera (2011), Conde Diaz et al (2009) and Dalgalarrondo et al (2003). In every hospital analyzed, the diagnosis focuses on the medical assessment, being conducted unilaterally by the prescriptions provided by their psychiatrists with views to the information collected, allowing the mitigation of psychic disorganization characteristic of crisis situations.…”
Section: Analysis Axis II -Diagnostic Criteriasupporting
confidence: 88%
“…Little is known about the organization of emergency teams, considering problems they face on a daily basis or their abilities to establish connections with the substitute services (Brasil, 2010;Del-Ben & Teng, 2010). Among the national studies, we include the study by Dalgalarrondo, Botega and Banzato (2003), who conducted a data collection of 2,047 consecutive admissions in a psychiatric unit in the metropolitan region of Campinas, with a view to socio-demographic and clinical variables associated with the success or failure of hospitalization; a study conducted by Larrobla e Botega (2006) concerning the implementation of a therapeutic model of reference and current situation of psychiatric wards in general hospitals of various cities of Minas Gerais, Sao Paulo and Santa Catarina States, as well as the exploratory study of Cardoso and Galera (2011), who identified the common characteristics between patients that were recently discharged from psychiatric hospitalizations in the outpatient service of Ribeirao Preto city.…”
mentioning
confidence: 99%
“…A depressão pós-esquizofrenia -F20,4 (1% -48 pacientes) foi o acometimento a menos freqüente (Figura 4). Ferreira AAA et al artigo original Dalgalarrondo et al (2003) Pode-se verificar redução na incidência e no período de internação para os pacientes com esquizofrenia. Em 1999, os doentes internados pela psicose permaneciam 50 ± 36,2 dias.…”
Section: Análise Dos Dadosunclassified
“…Contudo, a internação psiquiátrica, a despeito das múltiplas controvérsias, continua sendo um recurso terapêutico indispensável (embora pontual) para muitos pacientes, sobretudo os mais graves (Dalgalarrondo;Banzato, 2003).…”
Section: Análise Dos Dadosunclassified
“…Today, professional mental health care is the result of many discussions and changes that led to the process of deinstitutionalizing patient care. In Brazil, psychiatric hospitals, the main location where these treatments occur, are no longer the basis of the health care system, giving space to a network of extra-hospital service network of increasing complexity (4)(5) . However, as it is an essential procedure composing health care and evolution of the major psychiatric illnesses, psychiatric hospitalization remains a widely used resource.…”
Section: Introductionmentioning
confidence: 99%